Beyond likes and follows understanding social media's grip on adolescent mental health - Jandevi, Uspal (Association for Scientific Computing Electrical and Engineering (ASCEE), 2025)
This study aims to examine the psychological effects of social media use on adolescents, with particular attention to how patterns of digital interaction influence symptoms of anxiety, depression, and self-esteem. It seeks to understand not only the extent of these effects but also the underlying mechanisms—especially the role of social comparison and the pursuit of online validation within the broader context of the attention economy. Adopting a mixed-methods approach, this research integrates quantitative data from a survey of 500 high school students aged 13–18 with qualitative insights drawn from in-depth interviews with 20 adolescents. The survey measures the frequency and intensity of social media use, emotional responses to online interactions, and self-reported mental health outcomes using validated psychological instruments. The qualitative component enriches the findings by exploring how adolescents interpret their online experiences, internalize digital norms, and navigate the pressures of social media culture. Findings indicate a significant correlation between high-frequency social media use and increased levels of anxiety and depressive symptoms, especially among female participants. Respondents frequently reported feelings of inadequacy, social pressure, and sleep disturbances linked to online comparison and fear of missing out (FOMO). The contribution of this research lies in its comprehensive and context-sensitive examination of adolescent social media engagement, offering both empirical evidence and theoretical insight into the psychosocial vulnerabilities exacerbated by digital platforms. By combining statistical trends with personal narratives, the study adds depth to ongoing discussions about youth mental health in the digital age. It further advocates for the development of digital literacy education and mental health interventions that are responsive to the lived realities of adolescents growing up in algorithmically curated social environments.